Infeksi Oportunistik pada Pasien HIV yang Dirawat Inap di RSUP Dr. Hasan Sadikin Bandung Tahun 2019-2022 - Salma, Katarina; Hartantri, Yovita; Fauziah, Nisa (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. Human Immunodeficiency Virus (HIV) is a virus that infects and attacks the human immune system. The high morbidity and mortality rates in HIV patients can be attributed to various factors, one of which is the presence of opportunistic infections due to the weakened immune response, making HIV patients highly susceptible to other infections. This study aims to provide an overview of opportunistic infections in HIV patients hospitalized at Dr. Hasan Sadikin General Hospital in Bandung within the period of 2019-2022. Methods. This descriptive observational study was conducted on 255 HIV patients with opportunistic infections who were hospitalized at dr. Hasan Sadikin Hospital (RSHS), Bandung. The study utilized secondary data from medical records from 2019 to 2022. The sampling method employed in this research was total sampling. Data processing and analysis of the relationship between two variables, namely the number of opportunistic infections and length of hospital stay, with HIV stage, were performed using IBM SPSS Statistics software version 26. The statistical methods used in this analysis included the Chi-square test and the Mann-Whitney test. Results. The research findings indicated that the most common opportunistic infection in HIV patients was oral candidiasis (60,0%), followed by pulmonary tuberculosis (453,1%) and toxoplasmosis (45,136,5%). The prevalence of opportunistic infections was higher in males (79,2%) compared to females. The age group most affected was patients aged 24-44 years. There was also a significant association between the HIV stage and the number of opportunistic infections, with a higher number of opportunistic infections occurring in patients with stage 4 HIV. Conclusions. Oral candidiasis and tuberculosis are opportunistic infections with the highest prevalence among HIV patients who were hospitalized at dr. Hasan Sadikin Hospital during the period of 2019-2022.